THE EFFECTIVENESS OF NURSE-LED MOBILE HEALTH UNITS IN DELIVERING PRIMARY CARE SERVICES TO GEOGRAPHICALLY ISOLATED POPULATIONS - Albandari Thamer Alruwaili, Awaji Mohammed Madkhali, Amer Abdullah Al Assiri, Rafiah Obaid Shafi Alsamrah, Munirah Aql Shutayt Almutair, Mohammed Nasser Almutire, ,; Nasser Hamad Aljebreen, Mashael Mahdi Hamad Alqahtani, Mohammed Abdulrahman Alkhoraif, Ahmed Hadi Mohammed Bakkary, Malak Turki Alrwele, Ashwaq Mohammed Mohammed Jeteem,,; Amani Fayez Basheer Alfuhigi, Mohammed Yousef Mohammed Saeed, Hassan Mohammed Tomihi, (Chelonian Research Foundation, 2022)
Internationally, there is a growing emphasis on managing patients who need long-term and intricate care due to the rising prevalence of chronic illnesses. These patients need more extensive treatment for extended periods of time. The rise in chronic ailments has exerted financial and physical strain on healthcare systems, resulting in modifications to care delivery methods, with an emphasis on avoiding hospitalization and promoting home-based treatment. Nurses have a crucial role in coordinating care across many providers within this context. This evaluation was conducted as part of a financed research that examined the function of nurse navigators in a planned 24-hour telephone-call service. The study focused on a specific regional area with a varied population in terms of cultural identity and physical location in relation to accessing healthcare services. The study examines the existing research on the nurse's involvement in providing afterhours telephone assistance for patients with chronic and complicated diseases. The primary objective was to investigate the efficacy of treatments provided to patients residing in remote geographical areas. The implementation of an after-hours telephone service, regardless of the specific model used, should be consistent with a Chronic Care Model. After-hours telephone services staffed by competent nurses, who receive continuing professional development and follow appropriate procedures, contribute to the continued enhancement of chronic and complicated care management as a health priority. Keywords: Chronic disease, nurse intervention, telephone assistance, telephone service.